Determinan Prolonged Length Of Stay (PLOS) ICU pada Pasien Pediatrik yang Menjalani Pembiusan Di Masa Pandemi Covid-19 - Hernawan, Agung Diky; Sari, Djayanti; Widyastuti, Yunita (Jurnal Komplikasi Anestesi, 2022)
Background: In Indonesia, the utilization of ICU is not balanced, due to the limited ICU space or the length of time ICU patient care. ICU services include patients with organ dysfunction or post-anesthesia patients, especially pediatrics. Period 1 March 2020 Indonesia was hit by the COVID-19 pandemic. The need for ICU space increases, most of the infected patients fall into respiratory failure conditions both adults and pediatrics. Problems that are interconnected and become the basis for researchers in determining the determinants of PLOS ICU are post-anesthesia pediatric patients who need ICU care, limited ICU space and the problem of the COVID-19 pandemic. Objective: To identify the determinant factors of ICU Prolonged Length of Stay (PLOS) in pediatric patients undergoing anesthesia during the COVID-19 pandemic. Method: This research is a retrospective cohort observational study. The study sample was 173 pediatric patients undergoing anesthesia and postoperative care in the ICU at Dr Sardjito General Hospital for the period April 2020 - March 2021. The variables were tested using Student's t-test for numerical data, Chi square test for categorical/dichotomous data. The results of p <0.25 were followed by a logistic regression test. The results of p<0.05 were entered into the multivariate analysis and were considered significant. Results: The factors identified as the determinants of PLOS in the ICU Dr. Sardjito General Hospital were major surgery with a P value of 0.048 (OR 8.87), blood transfusions with a P value of 0.019 (OR 2.34) and mechanical ventilation with a P value of 0.010 (OR 3.44) ) is the most significant variable on PLOS in the ICU with a p<0.05. Conclusion: Major surgery, blood transfusions and mechanical ventilation/ventilators are the determinants of PLOS in the ICU of Dr. Sardjito General Hospital, pediatric patients undergoing anesthesia during the COVID-19 pandemic